To study the relationship between service quality and customer satisfaction of Y- Centre / Mohd Norman Junit and Mohammad Harith Azaman - Junit, Mohd Norman; Azaman, Mohammad Harith (Faculty of Business and Management, 2016)
Service quality and customer satisfaction are vital to an organization which run, build devotion, expand benefit and enhance business of the organization. This proposition shows a study, in which activity is being made in enhancing service quality and customer satisfaction of Y-Centre. This is on account of there was no examination led to break down the satisfaction of the customers of the organization. In principle parts are depicted five determinants of good service quality which are reliability, tangibility, assurance, responsiveness, and empathy. The intension of the examination study was to discover the relationship between service quality and customer satisfaction of Y-Centre. This exploration entitled "Relationship between service quality and customer satisfaction of Y-Centre in UTC Malacca" had been led to acquire results and discoveries. There are 170 questionnaires were circulated to the respondent and the researcher figured out how to get back completely replied of 150 questionnaires. Likewise, different wellsprings of information additionally have been use as a referral to reinforce the issues on the exploration study. This research closes with exchange on these outcomes, study impediment and proposal to the organization and future exploration headings.